Negosiasi Identitas Kekristenan dalam Ritual Kampetan di Watu Pinawetengan Minahasa - Gratciadeo Tumbelaka; Izak Y. M. Lattu; David Samiyono (Anthropos: Jurnal Antropologi Sosial dan Budaya (Journal of Social and Cultural Anthropology), 2020)
This article aims to preserve the Minahasa cultural identity in the presence of Christianity. The problem is focused on the determination of the identity of the community practicing ritual culture that is boldly demonstrating the cultural identity of the Minahasa people who have identified Christianity. The ritual ritual itself is an ancient practice of belief that is almost gone. To maintain the identity of the community in the midst of Christianity, people still do it. Ritualists negotiate their Christian identity in practice. Identity can flexibly adapt to an individual's circumstances. Therefore, together the existence of Christianity cannot kill culture and culture cannot reject the existence of Christianity. To approach this problem, Rappaport's theoretical references to rituals are used as a form of communication, Benwell and Stokeo's about identity theory as a matter of self-determination, and Burke and Stets about identities that determine the role of individuals where they are. In addition, the authors use the theory of identity negotiation from Ting-Toomey to see individual self-adjustment in other matters around it. Data was collected through field research at the research location in Watu Pinawetengan in Minahasa Regency, through interviews with ritual practitioners and analyzed qualitatively. This study concludes that, the existence of culture and Christianity in Minahasa goes together to develop cultural identity but also Christianity.